An Analysis of Figurative Language Elements upon an American Short Story Entitled “The Monkey’s Paw: Analisis Unsur Bahasa Kiasan pada Cerpen Amerika Berjudul “The Monkey’s Paw - Mandarani, Vidya; Ardiansyah, Nur Muhammad (JEES (Journal of English Educators Society), 2018)
This article describes the study of semantic in a specified domain of figurative language upon a selected work of American English literature, in form of short story written by the renowned writer and author, William Wymark Jacobs, entitled as ‘The Monkey’s Paw’. Several objectives are deduced by the researcher in quest of finding the forms of this figurative language within the passage. Briefly, figurative language itself is a feature of every languages, which emphasized the use of expression to symbolize a different meaning from the usual literal interpretation. In our analysis of ‘The Monkey’s Paw’, the varieties of figurative language: Metaphor, Personification, Hyperbole, Symbolism, also another terms used to represent unusual words construction or combination such as Onomatopoeia, Idiom, and even Imagery, are discussed in order in relation with true meaning discovery behind each figurative language properties.